Physiological Basis for Differential Selectivity of Four Grass Species to Aminocyclopyrachlor. Issue 4 (December 2015) - Parker, Ethan T.; Wehtje, Glenn R.; McElroy, J. Scott; Flessner, Michael L.; Panizzi, Peter
Abstract : Aminocyclopyrachlor (AMCP) is a synthetic auxin herbicide used for broadleaf weed control in pasture and rangeland. The tolerance and fate of AMCP within pertinent grass species is not well understood. Research was conducted to establish the tolerance of four grass species to AMCP application and observe their absorption, translocation, and metabolism. Results indicate that tall fescue is the most tolerant of AMCP at rates required for weed control. Bahiagrass and bermudagrass are marginally tolerant, and cogongrass is the most sensitive. Tall fescue and bahiagrass absorbed more AMCP than bermudagrass and cogongrass, but cogongrass absorption is the most rapid and complete within 2 days after treatment (DAT). Cogongrass and bermudagrass translocated the least amount out of the target area, whereas bahiagrass and tall fescue translocated the most. Radioisotope imaging revealed that tall fescue may sequester absorbed AMCP in leaf tips. This sequestering may be the basis of the greater tolerance to AMCP by tall fescue relative to the other species evaluated. No metabolism of AMCP was detected in any grass species out to 42 DAT.